Modelos agroflorestal, biodinâmico e manejo animal propostos para a escola Família Agrícola de Ladeirinhas "A", Japoatã/SE - Araújo, Itamara de Paula Andrade (2021)
This dissertation adressess about the possibilities of changing the agricultural practics in the school Família Agrícola de Ladeirinhas "A" considering the ecological models in the Sintropic Agroflorestrial System and biodynamic, as well as the insertion of biocentric and bioethical principles to the animal handle in the agriculturalpractics. It seeks to sensitize and encourage a rethinking in the way of deal with the land and its beings, mediated by the paradigm of the deep ecology/ buen-vivir, in order to develop empathy, respect qnd compassion to all kind of life forms. Its main objective is to contribute to the redefinition of the current agricultural practics um the EFAL.Specifically, study ecological agricultural models under the light of Deep Ecology; research integral formation of the pedagogy of alternancy aplied to EFAL; observe according to the Internal regiment, the PPP, the Curriculum Matrix and the agricultural practics experienced within the scope of EFAL; study the resignificatives possibilities of the biodinamic calendar to the practics in the EFAL. As a product, a pedagogical notebook for agricultural practices in the Sintropic Agroforestry System was created, with one agricultural biodinamic calendar. The proposed location for the study was the Family Agricultural School of Ladeirinhas, located in the village of Ladeirinhas “A”, in the municipality of Japoatã/SE. The methodology aplied to carry out the research consisted, in essence, in the aplication of bibliographic research, plus documentary research aligned with the phenomenological approach. With regard to the type of research, considering the objectives, this dissertation adopted the descritive type. As a result, ecological models based on the emerging ecological paradigm were obtained, which enabled the redefinition of EFAL practices, considering the principles of the pillar of comprehensive training. The documental observation of the Internal Regiment brought the possibility of resignification of agricultural practices in line with the principles of alternation pedagogy in its pillar of comprehensive training. Based on the observation of practices, according to the Curriculum Matrix, it can be concluded that they distance themselves from ecological agricultural models, especially with regard to animal care. Therefore, the resignification proved to be possible to be contemplated, considering the models elaborated by Rudolf Steiner and Ernst Götsch, proposed in the research.